Consumption Restriction in a Total Control Institution: Participatory Action Research in a Maximum Security Prison. (September 2015) - Hill, Ronald Paul; Rapp, Justine M.; Capella, Michael L.; ,
The marketing and public policy field has a long history of examining consumer decision making under conditions of abundance, but less effort has been dedicated to learning about restrictions to choice, especially as imposed by institutional forces. To help fill this gap in the literature, the authors offer an ethnographic investigation of a maximum security prison conducted over an 18-month period using participatory action research. This environment is a total control institution where depersonalization and commoditization of the 4, 000 men in its charge regularly occur. The findings reveal a complex relationship between these processes and various psychological reactions and resulting behaviors that are acted out within and outside the prison's licit and illicit marketplaces. The article closes with a discussion of theoretical implications of consumer constraint and a presentation of public policy implications.